(untitled) (Revista Contexto & Educação, 2022)
Environmental education (EA) viewed from the emancipatory and liberating viewpoint is one that takes into account ethical, aesthetic, political, economic, cultural and environmental aspects. In this sense, AS as a cross-cutting, is between, crosses and projects beyond the disciplines of the curriculum, being a transversal axis and triggers problems whose reflections are beyond the knowledge contained in a single curricular discipline. Within this conception, will the pedagogical coordinators who work in the municipal public schools of a city in the Paraíba Valley understand EA in this transversal perspective? The approach of this research was the application of a structured questionnaire elaborated on a Likert scale with Kruskal Wallis variance test and Student Newman-Keuls post-test to the 41 pedagogical coordinators of the teaching network in question. To better understand the results, the coordinators were divided into three groups, the ones that work in rural, urban and central and urban and peripheral schools. The results pointed to a conception of the coordinators for a pseudotransversality indicating that as conception there is an understanding of the necessity of an approach of this theme in the transversal field, but that in the daily practice it does not occur, implying in the educative action fragmented, cognicist and massified.